Environmentally friendly forest industry? : Motives and strategies for environmental responsibility - Silvennoinen, Marianna (My University, 2018)
Environmental responsibility has become a major part of companies’ corporate social responsibility (CSR) functions and its’ role has been growing especially during the past decade. Reasons for the development include public concern for the environment caused by global warming and other environmental threats. Due to the nature of its’ operations, forest industry has been facing intense pressure for environmental responsibility and has been developing the business into a more sustainable direction. Thus, the purpose of the research is to study the environmental responsibility approaches of forest industry multinational enterprises (MNEs). The purpose is further divided into three sub-objectives: • What is the role of environmental responsibility in the forest industry? • What motives do forest industry MNEs have for environmental responsibility? • What environmental strategies forest industry MNEs apply? The research was conducted as a qualitative interview study by interviewing three environmental responsibility specialists from two forest industry MNEs, three environmental responsibility consultants and two local stakeholders on environmental issues related to forest industry in order to get a broad perspective on the current state of the topic. In addition to the interview data, secondary data sources were used to complement the data. The findings of the research suggest that environmental responsibility has a special role in the forest industry and a lot of attention is paid to certain issues, such as environmental reporting and material and energy efficiency. Forest industry companies have various motives for implementing environmental responsibility, including environmental values, stakeholder pressures, and hopes for increased performance, which can be simultaneous and lead to proactive or reactive environmental strategies. The study indicates that even though environmental values have been gaining more foothold in corporate decision-making, stakeholder pressure is the most influential driver for environmental responsibility in the forest industry, followed by performance-driven motives emphasizing the importance of cost savings. In addition, the environmental responsibility strategies of forest industry MNEs seem to be combinations of reactive and proactive approaches, implying that some environmental issues are more proactively handled than others. Furthermore, sustainability communication is an important tool for proactive companies, whereas a reactive strategy does not put much effort into communication. Both stakeholder- and value-driven motives are driving forest industry MNEs towards proactive environmental actions, whereas the lack of stakeholder pressures and mere performance-driven motives can be associated with a more reactive approach.
Keywords: Ympäristövastuu, ympäristövastuumotiivit, ympäristövastuustrategiat, ympäristöviestintä, metsäteollisuus